2014
DOI: 10.1109/lsp.2013.2290192
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Point Belief Propagation

Abstract: The sigma point (SP) filter, also known as unscented Kalman filter, is an attractive alternative to the extended Kalman filter and the particle filter. Here, we extend the SP filter to nonsequential Bayesian inference corresponding to loopy factor graphs. We propose sigma point belief propagation (SPBP) as a lowcomplexity approximation of the belief propagation (BP) message passing scheme. SPBP achieves approximate marginalizations of posterior distributions corresponding to (generally) loopy factor graphs. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 17 publications
2
74
0
Order By: Relevance
“…However, this approach implicitly assumes a Gaussian ranging error distribution and thus is less accurate in typical indoor applications where the ranging errors are not Gaussian distributed. Similar observations can be made about [17], [21], which are also based on Gaussian ranging error models. In contrast, the proposed approach is more general and more suitable for indoor applications.…”
Section: B Computation Of Messagessupporting
confidence: 60%
See 2 more Smart Citations
“…However, this approach implicitly assumes a Gaussian ranging error distribution and thus is less accurate in typical indoor applications where the ranging errors are not Gaussian distributed. Similar observations can be made about [17], [21], which are also based on Gaussian ranging error models. In contrast, the proposed approach is more general and more suitable for indoor applications.…”
Section: B Computation Of Messagessupporting
confidence: 60%
“…The mobile nodes were assumed to have obtained the multihop distances to anchors using the DV-distance algorithm. • SPBP: sigma point belief propagation of [21] based on Gaussian ranging error model 3 in Table I. A similar approach as in [21] was employed to choose the prior distribution of each node's position, with the initial position variance set to 10.…”
Section: A Locating Static Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Bayesian belief propagation for cooperative localization suffers from the complexity arising from exchanging messages. Authors in [55] showed a sigma point belief propagation by which a low-complexity approximation can be achieved.…”
Section: G Localizationmentioning
confidence: 99%
“…However, the parametric models must be specially tailored for different localization scenarios [4,5]. In sigma point belief propagation (SPBP), the belief propagation (BP) or sum-product algorithm (SPA) is reformulated in a higher dimensional space so that the belief update procedure turns to a nonlinear filtering process, which is addressed using the sigma point filters [6].…”
Section: Introductionmentioning
confidence: 99%